Effect of Black Soldier Fly Frass (BSFF) on The Growth and Yield of Cayenne Pepper (Capsicum frutescens L.) - Rizki Nor Amelia; Amnan Haris; Putri Dinda Muliana; Istiqomah Ifnan Fauziyyah; Tiara Damayanti; Jauha Khoirun Nisa; Zahra Rafidah (Jurnal Biodjati, 2024)
Cayenne pepper is a leading horticultural commodity in Indonesia. However, the productivity and quality produced have not met market expectations. One of the contributing factors is the low quality of the soil. For this reason, switching from inorganic fertilizers to organic fertilizers, such as Black Soldier Fly Frass (BSFF), is necessary because it can provide several nutrients that are crucial in improving the soil's physical, chemical, and biological properties. In this study, the formulation of BSFF was tested for its impact on cayenne pepper's growth response and yield. The research was arranged in a completely randomized design consisting of three treatments with three repetitions, namely P1 (100 grams of BSFF biofertilizer), P2 (250 grams of BSFF biofertilizer), and P3 (500 grams of BSFF biofertilizer). The results showed an interaction between doses of  BSFF biofertilizer on plant height, physical conditions (color and size), number, and wet weight of cayenne pepper; which P3 gave the most optimal growth response and yield. In contrast to these results, all treatments reduced vitamin C  to the high level of N nutrients in BSFF biofertilizer. Therefore, further research is needed to find the right dosage (below 100 grams/500 grams of media) so that cayenne pepper has a high vitamin C.